Expression of estrogen receptor α and estrogen receptor β in fine needle aspirates of breast carcinoma - Kapila, K.; Anim, J.T.; Francis, I.M.; Al-Mulla, F.; George, S.S.; Behbehani, A.I.F. (Acta Cytologica, 2010)
Objective: To evaluate the expression of estrogen receptor β (ERβ) in fine needle aspirates (FNAs) and correlate the findings with its expression in tissue sections. Study Design: In 38 cases of breast carcinoma, expression of estrogen receptor α (ERα) and ERβ in aspirates and tissue sections was correlated with the cytologic and histologic grade of the tumor. Results: ERα and ERβ were expressed as nuclear staining in 80% and 90% of the cases in tissue sections and 47% and 45% of the cases in aspirates, respectively. Tissue expression of ERα (grade 1, 81%; grade 2, 100%) and ERβ (grade 1, 94%; grade 2, 100%) was greater than in grade 3 tumors (ERα, 50%; ERβ, 70%). In FNAs they were equally distributed in the different cytologic grades. In aspirates 30% of ERα negative tumors were positive for ERβ, while in tissues 75% of ERα-negative tumors were positive for ERβ (p=0.007). Conclusion: Demonstration of ERβ on FNA smears is feasible. It helps identify the specific subcohort of ERβ-positive tumors in ERα-negative breast cancers; that may have therapeutic importance.
Keywords: Aspirations biopsy; Breast cancer; Estrogen receptor α; Estrogen receptor β; Fine-needle